2014
DOI: 10.1007/s00125-014-3307-8
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of circulating glucose, insulin and NEFA on cardiac triacylglycerol accumulation and myocardial insulin resistance in a swine model

Abstract: Aims/hypothesis Cardiac steatosis and myocardial insulin resistance elevate the risk of cardiac complications in obesity and diabetes. We aimed to disentangle the effects of circulating glucose, insulin and NEFA on myocardial triacylglycerol (TG) content and myocardial glucose uptake. Methods Twenty-two pigs were stratified according to four protocols: low NEFA+low insulin (nicotinic acid), high NEFA+low insulin (fasting) and high insulin+low NEFA± high glucose (hyperinsulinaemia-hyperglycaemia or hyperinsulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Our results indicate that even in metabolically healthy subjects cardiac fat depots affect heart function, without being confounded by elevated circulating plasma substrate concentrations. This is of special interest, since the influence of circulating substrates or underlying metabolic disease on cardiac lipid stores is well established in animal models [ 25 ] as well as in humans [ 12 14 ]. Therefore we decided to include only metabolically healthy volunteers, to primarily elucidate the role of different cardiac fat depots as such.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that even in metabolically healthy subjects cardiac fat depots affect heart function, without being confounded by elevated circulating plasma substrate concentrations. This is of special interest, since the influence of circulating substrates or underlying metabolic disease on cardiac lipid stores is well established in animal models [ 25 ] as well as in humans [ 12 14 ]. Therefore we decided to include only metabolically healthy volunteers, to primarily elucidate the role of different cardiac fat depots as such.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the lack of a significant correlation between MYCL and parameters of LV heart function might most likely be explained by the low amount of ectopic lipids in a metabolically healthy lean population. MYCL develops on the background of hyperglycemia and hyperinsulinemia [ 13 ] combined with increased FFA concentrations [ 25 ], a metabolic condition that is not present in insulin sensitive normal weight subjects. On the other hand, PERI extends over a much broader range compared to MYCL in healthy volunteers, wherefore associations can be detected earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous reports [2,3] we showed that hyperglycemia was linked to cardiac steatosis. Interestingly, data from recent animal study [25] indicate that hyperglycemia increases myocardial glucose uptake by glucose mass action independently of insulin. Notably, in a recent study including subjects with and without the metabolic syndrome, myocardial steatosis was unrelated to antilipolytic and glucoregulatory actions of insulin [26].…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with type 2 diabetes, a 3-day very lowcalorie diet (471 kcal/day, but with SFA .13%) induced an increase in myocardial TG levels and reduced diastolic function, but with no change in LVEF measured by MRI (41). Fatty acid uptake by the heart is essential for intramyocellular TG repletion and the maintenance of cardiac function (42,43). It is therefore premature to postulate that enhanced cardiac DFA partitioning can be mechanistically linked to a reduction in LVEF in the current study.…”
Section: Discussionmentioning
confidence: 99%